Steroid response in primary childhood nephrotic syndrome in a tropical African environment (2020)
Background: Earlier studies on childhood nephrotic syndrome (NS) in tropical Africa showed steroid resistance in the majority. More recent studies show a variable picture, necessitating a re‑evaluation. This study was aimed at determining the current pattern of steroid response in childhood NS, in an environment known to be dominated by steroid resistance. Patients and Methods: This prospective study of consecutive children who received steroid therapy for primary NS was carried out at the University College Hospital, Ibadan, Nigeria between 2006 and 2013. The outcomes of interest were steroid sensitivity and death. The recruited patients received a 4-6 weeks’ course of prednisolone at 60 mg/m2/day followed by alternate day doses of 40 mg/m2 up to total steroid therapy duration of 6 months in steroid sensitive patients. Statistical analysis was carried out using STATA version 12.0. P value <0.05 was considered significant. Results: Of 109 children that received steroids for at least 8 weeks, whose mean (SD) age was 7.9 (3.7) years, 69 (63.3%) were steroid sensitive. Those aged ≥6 years responded as well as those aged <6 years (P = 0.78). Boys were more likely to be steroid‑sensitive than girls, 65.2% versus 34.8% (P = 0.039). There was zero mortality among the patients studied. Conclusion: This study has shown a better steroid sensitivity of 63.3% in children with primary NS compared with the previously reported 36.8-42.9% in patients with highly selective proteinuria. This improved steroid response and zero mortality show a remarkable departure from the past.